Cognition and semiotic processing of luminous stimuli in various orders of the natural word - Caivano, Jose Luis Ricardo (2015)
Semiosis, and particularly visual semiosis, is not something unique to humans. All animal species, all living beings (including other forms of life outside the animal kingdom) have semiotic activity. But we can go even beyond that. It is possible to maintain that also in the world that is usually called “inanimate” or “inert” some kind of semiotic activity takes place. This paper proposes a view in which the elements and organisms in the natural environment, instead of being classified into separate categories are thought of as forming a continuous gradation from one to another, from lower to upper levels of complexity and semiotic behavior. From this, and from further arguments, it is possible to maintain that semiosis permeates the entire universe. A special point is made concerning the interaction of light stimuli with matter and living organisms, which in some cases has produced the systems of vision that many animals posses, and in some other cases produce reactions and changes that can be considered as a kind of protosemiotic activity.